2005
DOI: 10.1530/eje.1.02052
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin serum levels in children with type 1 diabetes: a potential modulating role in bone status

Abstract: Objective: Children and adolescents with type 1 (insulin-dependent) diabetes mellitus (T1DM) show several impairment of bone metabolism and structure, resulting in a higher risk of decreased bone mass and its related complications later in life. Alterations of the nuclear factor-kB ligand (RANK-L)/osteoprotegerin (OPG) system have been implicated in several metabolic bone diseases characterized by increased osteoclast differentiation and activation and enhanced bone resorption. Design: We aimed to assess OPG l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 67 publications
(58 reference statements)
8
50
3
6
Order By: Relevance
“…This was first shown by Browner et al [12], who reported that although no associations were seen between the bone parameters and plasma osteoprotegerin levels, individuals with diabetes as well as persons with cardiovascular disease had increased values. Since then, these findings have been confirmed in both type 1 [38,39] and type 2 diabetes [13,40]. Moreover, we recently found that plasma osteoprotegerin is increased in subgroups of type 1 diabetic patients with nephropathy and in subgroups with signs of cardiovascular disease [18].…”
Section: Discussionmentioning
confidence: 57%
“…This was first shown by Browner et al [12], who reported that although no associations were seen between the bone parameters and plasma osteoprotegerin levels, individuals with diabetes as well as persons with cardiovascular disease had increased values. Since then, these findings have been confirmed in both type 1 [38,39] and type 2 diabetes [13,40]. Moreover, we recently found that plasma osteoprotegerin is increased in subgroups of type 1 diabetic patients with nephropathy and in subgroups with signs of cardiovascular disease [18].…”
Section: Discussionmentioning
confidence: 57%
“…[13][14][15][16][17][18] Therefore, to further analyze whether the serum levels of OPG were affected by hyperglycemia and/or by other aspect of the metabolic disorders associated to diabetes mellitus, such as hypercholesterolemia, the next experiments were performed in the apoE-null mice, 26 which are characterized by elevated levels of total serum cholesterol (mean Ϯ SD, 14.27 Ϯ 2.1 mmol/L) with respect to littermate mice (mean Ϯ SD, 1.81 Ϯ 0.42 mmol/L). In these animals, STZ-induced diabetes mellitus was associated to the development of widespread aortic atherosclerotic lesions, starting from 10 to 12 weeks from diabetes induction onwards ( Figure 3A).…”
Section: Correlation Between Opg Serum Levels and Hyperglycemia In DImentioning
confidence: 99%
“…3,5 It has been shown that OPG is produced by a wide range of tissues, including the cardiovascular system, and that OPG levels are particularly high in aortic and renal arteries. 10 -12 Interestingly, different groups of investigators have reported that serum OPG is significantly increased in both type 1 and type 2 diabetic pa-tients, [13][14][15][16][17][18] as well as in both diabetic and nondiabetic patients affected by coronary artery disease. [17][18][19][20] Moreover, it has been demonstrated that up-regulated serum OPG levels have a negative prognostic value in heart failure after acute myocardial infarction as well as in patients affected by abdominal aortic aneurysm.…”
mentioning
confidence: 99%
“…Using an activity questionnaire, physical activity was assessed with a modified activity score composed of the scores for sports/leisure activities (0, !2 or O2 h/week), as previously described (14).…”
Section: Case Definition and Study Protocolmentioning
confidence: 99%
“…Calcium dietary intake was assessed with the semiquantitative validated food frequency questionnaire (14). Selection of items was based on the food composition diet, frequency of use and relative importance of food items as a calcium source.…”
Section: Case Definition and Study Protocolmentioning
confidence: 99%